Periodic Solutions for Nonlinear System of Differential Equations of Third Order with Boundary Conditions - Raad N. Butris; Ghada Shuker Jameel (College of Education for Pure Sciences, 2013)
ABSTRACT In this study we investigate the existence and approximation of the periodic solutions for nonlinear system of differential equations of third order with boundary conditions. The numerical-analytic method has been used to study the periodic solutions of the ordinary differential equations that were introduced by Samoilenko. Also these investigation lead us to the improving and extending the above method and the results of Butris.